Empowerment of Village-Owned Enterprises in the Development of Tourism Villages to Increase Community Income in the Turpuk Limbong Samosir Tourism Village, North Sumatra - Revida, Erika; Badaruddin (Talenta Publisher, 2023)
Empowering Village-Owned Enterprises (BUMDes) in developing tourist villages is one solution to increase the income of the people of the Turpuk Limbong Samosir tourist village, North Sumatra. The aim of this community service was to empower BUMDes and increase their knowledge and abilities in developing tourist villages to increase community income in the tourist village of Turpuk Limbong Samosir, North Sumatra. This service to the community started from carrying out preliminary mapping or surveys to the location, namely the tourist village of Turpuk Limbong Samosir, North Sumatra. Then collaborate and approach the BUMDes Turpuk Limbong management chaired by Betania Exaudi Sinaga, SP. The Community Service Team provided an explanation about the importance of empowering BUMDes in developing tourist villages to increase community income in the tourist village of Turpuk Limbong Samosir, North Sumatra. The method of activities carried out starts from providing education through training, simulation and mentoring for several days to BUMDes administrators and the community in developing tourist villages to increase community income in the tourist village of Turpuk Limbong Samosir, North Sumatra and seeing changes in the knowledge, attitudes and behavior of the management of Owned Enterprises. Villages (Bumdes) and communities and apply the concepts that have been presented in training at the tourist village of Turpuk Limbong Samosir, North Sumatra. This community service received a full response and attention from the BUMDes management and the community in the tourist village of Turpuk Limbong Samosir, North Sumatra. This can be seen from their enthusiasm in listening to the service activities being carried out. They really hope that this activity can continue in the future. The results of this activity have been published in online media (newspapers) and videos of the activity have been uploaded to YouTube.